The UN Sustainable Development Goals and Provision of Security, Responses to Crime and Security Threats, and Fair Criminal Justice Systems (University of Maribor Press, 2024)
The book comprises 14 peer-reviewed chapters based on research on crime and security threats in relation to the United Nations Sustainable Development Goals. The book represents a multidisciplinary work that combines different views of safety and security provision in local environments, at the national level, as well as in the international environment. The chapters include findings of a literature review, empirical research on crime and victimization of individuals, case studies, specific forms of crime, institutional and civil society responses to security threats, as well as legal and police and policing perspectives in relation to safety and security provision in modern society. — This compilation stands apart from other books on the SDGs for its attention to Goal 16. The Introduction includes interesting reference to ways that criminology and criminal justice link to other SDGs (e.g., green criminology relates to Biosphere SDGs and human trafficking to economy SDGs). But the remaining chapters focus on SDG 16 in ways that provide the reader with useful, informative, and specific information on goal targets to reduce all forms of violence, combat organized crime, and establish effective criminal justice institutions. With examples from a variety of countries, settings, and crime types the editors have compiled a comprehensive and edifying review of material that will assist students, researchers, and educators in their various endeavors. Philip Reichel, PhD Professor Emeritus, University of Northern Colorado Past Chair, American Society of Criminology Division of International Criminology — The volume is edited by prominent scholars in comparative criminal justice and offers a timely contribution that considers, in part, progress toward the United Nations Agenda for Sustainable Development. The foundational material on the United Nations Sustainable Development Goals makes the multiauthor volume accessible to a wide readership. Although the collection centers on SDG 16—Peace, Justice, and Strong Institutions, considered together with the intersecting content on targets and indicators, and the inclusion of research from Brazil, several European countries, the United Kingdom, and the United States, the scope provides the possibility for larger discussions on global patterns and policies. The text would be a great option for global inquiry courses and provide students with opportunities to engage with the SDGs, while exploring what factors impact achievement of the UN Agenda for Sustainable Development, as well as global criminal justice reforms. Dawn Beichner-Thomas, PhD Professor, Criminal Justice Sciences, Illinois State University Chair, American Society of Criminology Division of International Criminology